Cárie da primeira infância: fatores associados e efetividade da aplicação tópica profissional de fluoretos - Oliveira, Patrícia Maria Costa de (2016)
Early Childhood caries (ECC) is the most prevalent disease in children between three and five years old. The use of index with technical advantages over historically used, such as International Caries Detection and Assessment System (ICDAS II), it is imperative for the management and early diagnosis of CPI. The CPI is avoidable and the topical application of fluoride is recommended as its progression control measure. The objectives of this thesis, formatted in two chapters were: 1) to investigate the correlation between dietary habits, oral hygiene and socioeconomic factors and the development stages of CPI. 2) conduct a systematic review of the literature on the effectiveness of professional topical fluoride application in control of CPI. In the first study, 163 children were examined according to the criteria of ICDAS II and divided into three groups: caries-free (n = 59), enamel caries lesions (n = 55) and dentin caries lesions (n = 49). The presence of clinically visible plaque was recorded, as well as the daily frequency of meals which contain sugar. Social factors were assessed by a questionnaire sent to those responsible. Data were analyzed by chi-square test, followed by multiple logistic regressions, considering p <0.05 and confidence interval = 95%. To the second proposition of the thesis, we proceeded to a systematic review of the literature held in electronic databases: Google Scholar, LILACS, IBECS, MEDLINE, Cochrane Library, SciELO and PubMed, from August 2015 to March 2016. The descriptors used in Portuguese and English were: tooth decay; child; primary tooth; efficacy and topical fluorides. Nine studies were critically evaluated for meeting the selection criteria. Of this total, five were excluded, resulting in four articles included in this systematic review qualitatively evaluated under the criteria of the PEDro scale (Physioterapy Evidence Database) and CONSORT (Consolidated Standards of Reporting Trials). Study 1 showed that age (OR = 3.67), use of dental services (OR = 3.44), mother’s literacy (OR = 4.55) and daily consumption of sugar (OR = 2.58) were associated significant with carious lesions in enamel. Age (OR = 3.26), visible plaque index (OR = 3.49) and frequency of brushing (OR = 4.55) were significantly associated with carious lesions in dentin. In the review, one trial indicated that professional application of fluoride varnish used in children significantly reduced the average increase of the group, but there is no agreement observed in other trials evaluated in this review. The conclusions is that cariogenic diet, hygiene and socioeconomic factors are associated with dental caries and caries prevalence increased with age of the individual, its percentage of visible dental plaque, as well as higher sugar consumption to six daily servings, the care provided by unschooled mothers and difficulty in accessing dental services. There is no scientific evidence attesting to the effectiveness of professional topical fluoride application in control of CPI.